Koncepcja nowego podejścia banku do finansowania przedsięwzięć realizowanych w ramach partnerstwa publiczno-prywatnego - Korenik, Dorota (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The study focuses on public-private partnership (PPP) project from the pointof view of a bank as a third party financing the PPP project. The aim of the studyis to present two different approaches a bank can adopt: the one currently usedby banks and an approach proposed by the author.